The Public Image of Big Business in America, 1880-1940 A Quantitative Study in Social Change - Galambos, Louis (Johns Hopkins University Press, 2019)
Otiginally published in 1975. At the time that Louis Galambos published The Public Image of Big Business in America in 1975, America had matured into a bureaucratic state. The expression of the military-industrial complex and big business grew so pervasive that the postwar United States was defined in large part by its citizens' participation in large-scale organizational structures. Noticing this development, Galambos maintains that the "single most significant phenomenon in modern American history is the emergence of giant, complex organizations." Today, bureaucratic organizations influence the day-to-day lives of most Americans-they gather taxes, regulate businesses, provide services, administer welfare, provide education, and on and on. These organizations are defined by their hierarchical structure in which the power of decision-making is allotted according to abstract rules that create impersonal scenarios. Bureaucracies have developed as a result of technological changes in the second half of the nineteenth century. Based on the premise that these structures had a stronger influence on modern America than any other single phenomenon, this book explores the public's response to the growth of the power and influence of bureaucracy from the years 1880 through 1930. What results is an examination of the social perception of bureaucracy and the development of bureaucratic culture.